Somatostatin analogs modulate AIP in somatotroph adenomas: the role of the ZAC1 pathway. - Chahal, H; Trivellin, G; Leontiou, C; Alband, N; Fowkes, R; Tahir, A; Igreja, S; Chapple, J; Jordan, S; Lupp, A; Schulz, S; Ansorge, O; et al. (2012)
CONTEXT: Somatotroph adenomas harboring aryl hydrocarbon receptor interacting protein (AIP) mutations respond less well to somatostatin analogs, suggesting that the effects of somatostatin analogs may be mediated by AIP. OBJECTIVE: The objective of the investigation was to study the involvement of AIP in the mechanism of effect of somatostatin analogs. DESIGN: In the human study, a 16-wk somatostatin analog pretreatment compared with no pretreatment. In the in vitro cell line study, the effect of somatostatin analog treatment or small interfering RNA (siRNA)/plasmid transfection were studied. SETTING: The study was conducted at a university hospital. PATIENTS: Thirty-nine sporadic and 10 familial acromegaly patients participated in the study. INTERVENTION: Interventions included preoperative lanreotide treatment and pituitary surgery. OUTCOME: For the human study, GH and IGF-I levels, AIP, and somatostatin receptor staining were measured. For the cell line, AIP and ZAC1 (zinc finger regulator of apoptosis and cell cycle arrest) expression, metabolic activity, and clone formation were measured. RESULTS: Lanreotide pretreatment reduced GH and IGF-I levels and tumor volume (all P < 0.0001). AIP immunostaining was stronger in the lanreotide-pretreated group vs. the surgery-only group (P < 0.001). After lanreotide pretreatment, the AIP score correlated to IGF-I changes in females (R = 0.68, P < 0.05). Somatostatin receptor staining was not reduced in samples with AIP mutations. In GH3 cells, 1 nm octreotide increased AIP mRNA and protein (both P < 0.01) and ZAC1 mRNA expression (P < 0.05). Overexpression of wild-type (but not mutant) AIP increased ZAC1 mRNA expression, whereas AIP siRNA knockdown reduced ZAC1 mRNA (both P < 0.05). The siRNA-mediated knockdown of AIP led to an increased metabolic activity and clonogenic ability of GH3 cells compared with cells transfected with a nontargeting control (both P < 0.001). CONCLUSION: These results suggest that AIP may play a role in the mechanism of action of somatostatin analogs via ZAC1 in sporadic somatotroph tumors and may explain their lack of effectiveness in patients with AIP mutations.